Інтимізація наративу засобами просторово-часової фокалізації - Палійчук, Анна Леонардівна; Paliychuk, Anna (Видавництво національного університету «Острозька академія», 2010)
У статті «Інтимізація наративу засобами просторово-часової фокалізації» проаналізовано вплив просторово-часової фокалізації на інтимізацію наративу; визначено способи її об’єктивації на поверхневому рівні тексту. The article “Intimisation of the Narrative by the Means of Spatio-temporal Focalization” analyzes the influence of the spatio-temporal focalization on the intimisation of the narrative; means of its objectification in the surface structure of the text are defined.
Intimisation of the Narrative by the Means of Spatio-temporal Focalization
Keywords: інтимізація; просторова фокалізація; часова фокалізація; наратив; дейксис; теперішній наративний час; intimisation; spatial focalization; temporal focalization; narrative; deixis; the present narrative tense